Uso de micro-ondas na síntese de novos (+/-) pterocarpanos com atividade sequestradora de radicais livres - Claiton Pires Ventura (2010)
This work describes a comparative study to obtain racemic pterocarpans by classical heat and a novel method using microwave: it was obtained seven racemic pterocarpans by cycloaddition [3+2], among them five are new. In this study it was proved the efficiency of the microwave heat, which allows yield enhancements and significant reduction of reaction time when compared to traditional methodology.To obtain different new compounds with potential biological application, eleven new pterocarpans were synthesized with different substituents in the ring A and D, among them ten were obtained by O-alkylation and one by hydrolysis of an esterificated product. Finally, a potential antioxidant activity of the (±) pterocarpans synthesized has been analysed by DPPH·(1,1-diphenyl-2-picrylhydrazyl) radical scavenging assay. This experiment was monitored by spectrophotometry employing resveratrol as the positive control. All pterocarpans with phenolic hydroxyl groups presented a significant scavenger activity confirmed by the DPPH· assay. These compounds presented better activities than the positive control resveratrol.